Crohn’s Disease linked Polymorphisms associated with Autophagy contribute to Th17 cell induction through increasing the expression of IL-1β and TNF-α - Daniel Clayton Morse (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
Genome wide association studies (GWAS) have linked polymorphisms in autophagy genes to Crohn’s Disease (CD). Interestingly, recent studies have shown that defective autophagy leads to increased levels of the cytokines IL-1b and TNF-a, which play a critical role in Th17 cell differentiation. This is significant because CD is marked by a Th17 cell mediated inflammatory response. This article examines the manners in which defective expression of autophagy linked proteins, can indirectly amplify and sustain Th17 cell induction through increasing the production of Th17 positively differentiating cytokines (IL-1b and TNF-a) and decreasing the production of a Th17 down regulating cytokine, IL-10.
Keywords: Immunology; Autophagy; Crohn& #x27; s Disease